Groundcover improves nutrition and growth of citrus trees and reduces water runoff, soil erosion and nutrient loss on sloping farmland - Liu, Rui; Zhang, Yuting; Wang, Zhichao; Zhang, Xueliang; Xu, Wenjing; Zhang, Jianwei; Zhang, Yueqiang; Hu, Bin; Shi, Xiaojun; Rennenberg, Heinz (Frontiers in Plant Science, 2024)
Groundcover management plays a crucial role in improving water retention and soil nutrition in orchard systems, thereby preventing environmental constrains by non-point source pollution. However, effectiveness of groundcover management in citrus orchards developed on sloping farmland with eroded purple soil has not been studied in detail. In particular, information on the soil nutrient losses, e.g., nitrogen (N) and phosphorus (P), through interflow and its effects on growth and nutrition of citrus plants has not been reported. The present study evaluated the effects of different cover crops, i.e., Lolium perenne L. (LoliumCL), Vicia villosa Roth var. (ViciaCV) and Orychophragmus violaceus (OryCO), on nutrition and growth of citrus trees as well as water, soil and nutrient retention in an orchard developed in sloping farmland during two consecutive years. The results show that the groundcover species LoliumCL and ViciaCV mediated nursing effects on nutrition and growth of citrus trees. These nursing effects included enhanced foliar levels of carbon(C), N and P as well as increased tree height, ground stem diameter, and crown breadthwidth. Groundcover management generally reduced the annual surface runoff, interflow, soil loss, total N loss and total P loss. Among the cover crop species studied, LoliumCL and ViciaCV were overall more efficient than OryCO in this context.LoliumCL reduced the average annual total loss of N and P by 42.53% and 49.23%, respectively, compared with clean tillage. The estimated annual reduction potentials of soil, N and P losses in Ssouthwestern China were 16.3, 3.4 and 8.5 million tons yr -1 , respectively. Obviously, LoliumCL and ViciaCV provide highly beneficial ground coverage on sloping farmland and, thus, can be used for future sustainable development of citrus orchards.